Nordic-Baltic security, Germany and NATO : the Baltic Sea Region is a test case for European security - Major, Claudia (2016)
Zusammenfassung: The countries around the Baltic Sea are among Europe's frontline states affected by the conflict between Russia and western Europe. The Baltics and Nordics share a common concern about a revisionist, aggressive, and rearming Russia: Since the onset of the crisis in and around Ukraine in 2014, these countries have felt increasingly exposed to Rus-sian military and non-military intimidation. Currently, they can neither defend nor maintain regional security by themselves: Their capacities are limited and their mem-ber-ships in different security institutions (EU and NATO) complicate a common assess-ment and response, as do their diverging security policies. They depend on the deter-rence and defence efforts of their partners and NATO. This has turned the regional Nor-dic-Baltic security challenge into a European and transatlantic one. NATO's credibility depends on whether it can guarantee the security of those countries. Germany, as one of the largest and most capable countries bordering the Baltic Sea, should contribute towards improving regional security by supporting regional cooperation, and by sharpening the Nordic-Baltic dimension of its security policy. (SWP Comments)